Implementation of Group Investigation (GI) Cooperative Learning Model to Improve Students 'Critical Thinking Skills in Biology Subject - Hikmawati Hikmawati; Asmawati Munir; Parakkasi Parakkasi (Journal of Biological Science and Education, 2020)
Students' critical thinking is needed, because during the learning process students develop ideas about the problems contained in learning. The aim of this research was to improve students' biology critical thinking skills. This research was conducted in the even semester of the 2013/2014 academic year. This type of research was classroom action research (CAR) with three learning cycles. The data sources of this research were an assessment using learning activity of observation sheets and student learning outcomes tests. The data obtained were analyzed using qualitative and quantitative data analysis. The success of the students’ activity action in cycle I with a mean score was 3.25 with percentage was 81.54%; Cycle II amounted to 3.2 with percentage of 80,05% and in cycle III amounted to 3.61 with percentage of 92%. Students' critical thinking skills in cycle I were 62.18 with percentage was 25.64%. The average achievement of students’ critical thinking skills test in cycle II was 83.08 with percentage was 94.87%. The average achievement of students' critical thinking skills test in Cycle III reached 85.38 with percentage 97.43%. Based on the results of the research conducted, it was concluded that the application of the GI type of cooperative learning model could improve the student’s activity and students' critical thinking skills in the material of the immune system at class XI IPA3 of Senior High School 2 Kendari.Keywords: Group Investigation, Student Activities, Critical Thinking.